USE OF THE EXPERT ASSESSMENT METHOD IN TECHNOLOGICAL EQUIPMENT OF AUTOMOBILE ENTERPRISES - Исломов, Шерзод (Научно-технический журнал «Машиностроение», 2024)
As a result of updating the current situation in the transport enterprises with modern cars, the elements of the production technical base do not meet the parameters of the car, or as a result of obsolescence of existing technological equipment and devices. the problem of adaptive rapid reconstruction occurs. Due to the high weight of factors that need to be taken into account in the development of the system of technological equipment of the trucking company in real production situations, there is insufficient information about the consequences of the decision made in these conditions.The use of the "expert assessment" method is one of the most effective ways to analyze the situation in the field where there is insufficient information about the consequences of the decision and to gather the opinions of qualified experts in making decisions.This article analyzes the essence of the method of achieving solutions to the problem by summarizing the opinions of leading experts using the "expert evaluation" method in the conditions of uncertainty and lack of information in motor transport enterprises